Extract from endophytic Fusarium isolates stimulates seed germination of the host and protocorm development of non-host orchids - Sujit Shah; Mukti Ram Paudel; Bir Bahadur Thapa; Harshita Sharma; Arun Kumar Kashyap; Bhagwan Narayan Rekadwad; Rohit Sharma; Jyotsna Sharma; Bijaya Pant (Communicative & Integrative Biology, 2025)
We isolated endophytic Fusarium strains from the healthy roots, stems, and leaves of Dendrobium moschatum to investigate their plant growth-promoting activities in vitro. Subsequently, Indole acetic acid (IAA) was quantified and the IaaM gene (responsible for IAA synthesis in fungi) was amplified and sequenced. Finally, a germination assay was performed with seeds of D. moschatum and a plant growth assay with protocorms of Dendrobium longicornu to test their plant growth-promoting activities. Five Fusarium isolates (CDS11, PDL1, PDL3, PDR6, PDR7) were identified in this study. The highest amount (60µgml−1) of indole acetic acid was recorded in the PDR7 extract, whereas it was not detected in PDR6 and CDS11. The fungal extracts of isolates PDR6 and PDR7 were highly effective for seed germination by approximately 80% and 90% (respectively) of the host plant. The fungal extract of PDR7 showed a high IAA content and promoted in vitro seed germination of the host (D. moschatum) and protocorm development of the non-host (D. longicornu). In contrast, IAA content in the fungal extract of PDR6 remained undetected but was effective in both seed germination and protocorm development. Our results demonstrated the potential beneficial application of endophytic Fusarium in orchid mass propagation.